More than 100 UMPSA alumni enliven Alumni Meet and Greet Programme - Nor Salwana, Mohammad Idris (UMPSA, 2025)
KOTA KINABALU, 30 April 2025 – More than 100 alumni of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) from various professional sectors attended and enlivened the UMPSA Alumni Meet and Greet Programme held at The Klagan Hotel, Kota Kinabalu.